2023
DOI: 10.1021/acsaom.3c00016
|View full text |Cite
|
Sign up to set email alerts
|

Cr-Doping-Induced Fano Resonance of ZnO-Layered Nanoporous Structures and UV Photodetector Application

Abstract: In this study, a layered nanoporous structure of Cr-doped zinc oxide (ZnO) was synthesized by a simple hydrothermal and post-annealing technique. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and ultraviolet (UV)−visible spectroscopy techniques. The XRD peak shift provides additional evidence of the incorporation of the dopant. Field emission scanning electron microscopy was used to confirm the porous morphology. From high-resolution transmission electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Unfortunately, most of the literature reports have agreed that pristine ZnO-based PDs exhibit slow response time because of the atmospheric adsorbates such as oxygen and water molecules, creating charge trap states on the surface . Therefore, a great effort has been devoted to improving the optoelectronic and photodetection properties of ZnO. The most common routes to enhance the photoresponse performance of ZnO-based PDs are doping of metals and preparing nanocomposites. In our previous research, flexible pristine and Mn-doped ZnO NRs (Mn/ZnO NR)-deposited MSM-type PDs were thoroughly investigated in terms of photoresponse time and detectivity . We observed that the photodetection parameters such as detectivity ( D *), responsivity ( R ), and response/recovery time have been improved by the Mn dopant.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, most of the literature reports have agreed that pristine ZnO-based PDs exhibit slow response time because of the atmospheric adsorbates such as oxygen and water molecules, creating charge trap states on the surface . Therefore, a great effort has been devoted to improving the optoelectronic and photodetection properties of ZnO. The most common routes to enhance the photoresponse performance of ZnO-based PDs are doping of metals and preparing nanocomposites. In our previous research, flexible pristine and Mn-doped ZnO NRs (Mn/ZnO NR)-deposited MSM-type PDs were thoroughly investigated in terms of photoresponse time and detectivity . We observed that the photodetection parameters such as detectivity ( D *), responsivity ( R ), and response/recovery time have been improved by the Mn dopant.…”
Section: Introductionmentioning
confidence: 99%